Greening practitioners worry about green gentrification but many don’t address it in their work - Lorien Nesbitt; Daniel L. Sax; Jessica Quinton; Leila M. Harris; Camilo Ordóñez Barona; Cecil Konijnendijk (Ecology and Society, 2023)
As cities attempt to ameliorate urban green inequities, a potential challenge has emerged in the form of green gentrification. Although practitioners are central to urban greening and associated gentrification, there has yet to be an exploration of practitioner perspectives on the phenomenon. We fill this gap with an online survey of 51 urban greening practitioners in Metro Vancouver and the Greater Toronto Area. Most respondents defined green gentrification as the displacement of vulnerable residents due to the installation or improvement of green space that attracts wealthy in-movers and increases property values. They were most likely to identify greening as driving green gentrification, with a minority identifying other systemic drivers with greening in a secondary role. Although 39 of 51 participants had some familiarity with green gentrification, most reported low confidence in their understanding of the concept, little evidence of using the concept in their work, and moderate concern that their work is implicated in green gentrification. The gentrification issues most encountered by practitioners were changes to neighbourhood character and uneven investment in public infrastructure, and those working in domains linked to planning, equity, and engagement were most likely to encounter gentrification issues. Practitioners experienced multiple barriers to addressing green gentrification, including limited institutional capacity, limited access to data and relevant information, policy/mandate restriction, and lack of engagement tools. Results indicate that practitioners have a moderate understanding of green gentrification but do not often use the concept in their work, despite their potential to contribute to or exacerbate it. This suggests some resistance to critiques of urban greening practice, a failure of scholarly critiques of urban greening to influence policy change, and the need for stronger research theory and research co-creation involving practitioners and academia.